Martius Graft Repair of Vesico-Vaginal Fistula: Experience at A Tertiary Care Center in Bangladesh - Sultana, Nargis; Begum, Rokeya; Yasmin, Farida; Akhter, Shamima; Sultana, Nazmin; Sharmin, Reshma; Begum, Khatija (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Vesico-Vaginal Fistula (VVF) is a pathology with severe social repercussions. Resolution of VVF can be achieved through multiple surgical, abdominal or vaginal techniques, which will generally depend on the fistula's characteristics and the surgeon's experience. In this study we describe our experience with vaginal approach to treat VVF using Martius graft repair. Materials and methods: This prospective observational study included 50 VVF patients operated in the fistula center of Chittagong Medical College Hospital, during the period of January 2013 to December 2014. The success rate and complications of Martius graft repair of VVF. Results: The leading age group was 26 to 35 years (50.0%) and age range from 16 to 60 years with a mean age of 32.1 (±SD 8.10) years. The majority (72.0%) was from low socioeconomic class and had short stature (64.0%).48% fistula was midvaginal, 28% was juxtracervical and 54% was <2 cm in size and 40% were associated with vaginal stenosis and urethral avulsion. In 36% cases postoperative complication were developed. 82% patients were fully cured, 6% cured with urethral incontinence, 2% cured with vaginal stenosis and in 10% cases surgery was failed. Conclusions: The vaginal technique for the treatment of VVF reinforced by Martius graft is safe and effective with low rate of complications. JCMCTA 2021 ; 32 (2) : 85-89